Bybelse getuienis oor homoseksualiteit – met ander oë gesien - Geyser, P. A. (HTS teologiese studies, 2002)
Biblical testimony on homosexuality – seen from another per-spectiveThe aim of this article is to (re)open the discussion of biblical testimony on homosexuality. The discussion focuses on the results of existing exegetical re-search. The article places the exegesis of the relevant Bible passages within the framework of the types of literature within which the references to same sex behaviour are found. Four categories of texts are usually cited by those who argue against homosexuality, namely: legal texts; narrative passages; lists or catalogues; creation reports. The case for a more careful translation and reading of the relevant texts, is advocated. A hermeneutics of suspicion and an engaged hermeneutics are needed to approach biblical testimony on homosexuality from a perspective of Jesus’ caring for those who have been wounded.